Application pressure in boom sprayer and efficiency of commercial fungal bioinsecticides - Guimarães, Cesar de Oliveira; Correia, Antônia do Carmo Barcelos; Ferreira, Marcelo da Costa (Pesquisa Agropecuaria Brasileira, 2004)
Fungal biopesticides are applied with conventional sprayers and this equipment may be inappropriate, and therefore affect field control efficacy of biopesticides. The objective of this research was to find out if the usual pressures used in the boom sprayers can affect the conidia pesticide activity of the Brazilian commercial entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae. Water fungi suspensions were passed through the equipment under three pressures (20, 40 and 60 psi) and evaluated for viability, virulence and conidia disruption. The viability was evaluated in slides covered by culture media after incubation at 26±0.5ºC and 12 hours photophase. The concentration was determined through Neubauer chamber count and the virulence to Diatraea saccharalis caterpillars was evaluated. In the three tested biopesticides no significant effect was found in any parameters. For the tested pressures, the boom sprayer does not affect the viability or virulence and does not destroy the conidia of the evaluated commercial biopesticides.
Keywords: Metarhizium anisopliae; Beauveria bassiana; microbial control; application technique; entomopathogenic fungi